Descriptive Review of Energy Performance Evaluation Approaches (Sains Humanika, 2016)
This study address energy performance evaluation uncertainities in design. To achieve energy efficiency in building, designer should incorporate energy performance evaluation approach to foresight energy performance failure during design. The research hasÂ  evaluated and compares the capabilities of energy performances evaluation approaches namely computational fluid dynamic approach, optimization algorithm, and coupled approach. Furthermore, descriptive review unveils the practical obstacles and challenges designers encounter during design life cycle and proposes future direction to mitigate inundated energy performance gap.
Keywords: Energy; design; performance; building envelope; simulation; optimization